Vila esperança: Luta por Moradia em Imperatriz-MA - MOREIRA, Glenda Almeida Matos (2022)
This research aims to examine, from the observation of the claim for housing Vila Esperança, in Imperatriz-MA, the construction of frames of injustice in documents, public statements and protests produced by residents and managers of the social movement. Therefore, a multi-sited methodology will be used, dealing with field and virtual research in contact with community leaders and archival research, in historical and journalistic documents. As central authors for understanding the theme, concepts built by Erving Goffman, William Gamson, David Snow, Robert Benford and Sidney Tarrow will be used, in addition to the use of these theories in the writings of professors Marcelo Kunrath Silva, Matheus Mazzilli Pereira and Jesus Marmanillo Pereira. Thus, the intention of these observations is the possibility of understanding the construction of the framing processes drawn from the claim for housing in the Vila Esperança community.